A Study of Noble Morals in the Implementation of the Project to Strengthen the Pancasila Student Profile in Mover Schools in Magelang Regency - Suryawan, Ari; Rasidi, Rasidi (Universitas Muhammadiyah Magelang, 2022)
Indonesian students often commit negative things. This depravity continued to happen in an aggregate number recently. One of the reasons is the lack of noble morals. This study intends to examine the Pancasila Student Profile program, especially for Elementary School Students, as an attempt to edify the students’ morals, which is one of the mandates in Merdeka Curriculum. Merdeka Curriculum provides fun learning experiences oriented in Indonesian people development. This study used mixed method approach. The research was conducted interactively, by which the data from different methods were confirmed to attain saturated data lead to the conclusion making. The data sources were 6 headmasters and 12 teachers from the teaching committee in sekolah penggerak (mover school) program. The data were collected by using questionnaire, interview, document review, and field study. The data were then analyzed by using descriptive, document review, and qualitative approach. The results showed that: 1) religious values were clustered into three, namely (a) religious values became the reference in operational curriculum design, (b) religious values were part of curriculum frameworks embedded in the Pancasila students profile, intra-curricular, school-characterized, and extracurricular activities, (c) religious values own 26% of place position counted from 5 subdimensions out of 19 subdimensions in the Pancasila student profile development phases. 2) the implementation of Pancasila student profile in sekolah penggerak (mover schools) follows six stages, namely understanding the project, setting up the school ecosystem, designing the project, managing the project, documenting the project and managing the project’s results, and evaluating as well as following up the project. 3) the supporting factors in internalizing the religious values in Pancasila student profile project were facilitator assistance and collaboration among schools, parents, societies, and the community of practitioners. Meanwhile, the inhibiting factors of internalization were the overlapping schools’ agendas, individual-centralized teachers’ workload, distribution, and participation of non-teaching committee teachers.